Melanotic schwannoma of the parotid gland in a child: a rare diagnostic challenge - Ahmad Shukri, fatin Aisya; Razak, Mohd Azfar; Nik Abdul Ghani, Nik Mohd Syukra; M. Rajet, Khairul Azhar; Johari, Ahmad Hafizuddin; Mohammad Azmi, Siti Norhafiza (Elsevier Inc., 2025)
Melanotic schwannoma is an exceptionally rare variant of nerve sheath tumors characterized by melanin-producing Schwann cells, accounting for less than 1% of all such tumors. Its occurrence in the pediatric population, especially within the parotid gland, is exceedingly uncommon and poses significant diagnostic challenges due to its clinical and histological overlap with other pigmented neoplasms. We present the case of a 12-year-old boy with a three-month history of a painless, progressively enlarging swelling at the left mandibular angle, initially misdiagnosed as parotiditis. Despite empirical antibiotic therapy, the mass persisted, prompting further investigation. Imaging revealed a well-defined mass in the superficial lobe of the left parotid gland, and surgical excision via total parotidectomy with selective neck dissection was performed. Histopathological examination confirmed the diagnosis of melanotic schwannoma, with typical spindle to epithelioid cell morphology and abundant intracytoplasmic melanin. Given the potential for aggressive behavior and recurrence, close multidisciplinary follow-up was instituted. This case highlights the importance of considering rare neoplasms in atypical pediatric parotid masses and underscores the need for comprehensive diagnostic and therapeutic strategies, including histopathological evaluation and long-term surveillance, to optimize outcomes.